Analisa Perancangan Sistem Pakar Untuk Mengidentifikasi Jenis Kulit Wajah - Santi , Indyah Hartami; Andari , Bina (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Artificial intelligence technology is utilized in all fields, one of which is the field of facial skin beauty. Women today often make mistakes in facial skin care, caused by determining the type of skin. From this phenomenon the role of software engineers to build an application that is able to identify the type of facial skin is very necessary. However, there are still many developers who do not design software properly, structured and systematically, so that applications that are built are not in accordance with user needs. The purpose of this study is to design a software system as a basis for building a software, especially an expert system. With this design it is expected to produce an application system that suits the needs of women to identify the type of facial skin so that they can carry out the right stature. The method / approach used is a method that produces a different method than the previous method, where the previous method still uses manual methods, and with this research produces modeling of computerized ways. Computerized system design modeling is built starting from system design analysis with the existence of a system flowchart, Data Flow Diagram and Flowchrat program. The results of the system design modeling are made a recommendation for software application builders in building expert systems with similar problems